International review of cytology : a survey of cell biology. - Bourne, Geoffrey H. (Geoffrey Howard), 1909-1988; Danielli, J. F. (James Frederic), 1911-1984; Jeon, Kwang W. (International review of cytology, 2007)
International Review of Cytology presents current advances and comprehensive reviews in cell biology - both plant and animal. Authored by some of the foremost scientists in the field, each volume provides up-to-date information and directions for future research. Articles in this volume include Mechanisms of Gradient Detection: A Comparison of Axon Pathfinding with Eukaryotic Cell Migration; Leptin and the Regulation of Hypothalamic-Pituitary-Adrenal Axis; Focal Adhesion and p53 Signaling in Cancer Cells; Cell and Molecular Biology of the Spindle Matrix; Mitochondrial Biology and Disease in Dictyostelium; Oxytocin and the Human Prostate in Health and Disease.